Genetic variability and ex situ conservation strategies for the neotropical tree Parkia platycephala Benth. - de Oliveira Silva, Dandara Yasmim Bonfim [UNESP]; de Farias, Séfora Gil Gomes; Resende, Rafael Tassinari; Cardoso, Clarice Ribeiro; Bezerra E Silva, Romário; Tambarussi, Evandro Vagner [UNESP] (Universidade Federal de Santa Maria, 2023)
Parkia platycephala, known commonly as faveira, is a native species that occurs widely throughout Brazil and has high nutritional value and ecological potential. The objective of this study was to estimate the genetic variability in a P. platycephala provenance and progeny test. The test was established using a randomized block design, with 45 progenies from three provenances. The evaluated quantitative traits included height (HEI), diameter at ground level (DGL), and diameter below the first bifurcation (DFB). The data were submitted to Restricted Maximum Likelihood/Best Linear Unbiased Prediction (REML/BLUP) analysis, from which estimates of genetic parameters, genetic correlations, BLUPs, genetic gains, and effective population size were obtained. Estimates of individual narrow sense heritability ( ) and within progeny heritability ( ) ranged from low to moderate (0.01 a 0.39), with the highest values observed for DGL (0.32 and 0.39, respectively). The coefficient of individual variation ( ) and between progeny genetic variation ( ) indicate the existence of genetic variability between and within provenances. The FST vaues demonstrate low to moderate genetic differentiation among the three populations, and genetic correlations between traits were all positive and significant. The results obtained show that there is genetic variability between the studied provenances and progenies. This ensures not only the ex situ conservation of the species, but it can also be exploited in breeding programs.
Variabilidade genética e estratégias de conservação ex situ para a espécie neotropical Parkia platycephala Benth.
Keywords: Faveira; Forest resources; Genetic parameters; Genetic resources